2019
DOI: 10.1111/jace.16802
|View full text |Cite
|
Sign up to set email alerts
|

Ablation behavior and mechanism of Cf/SiBCN composites in plasma ablation flame

Abstract: In this work, Cf/SiBCN composites are fabricated by an improved precursor infiltration and pyrolysis (PIP) approach. Ablation behavior of the Cf/SiBCN composites is investigated in plasma ablation flame at a heat flux of 4.02 MW m−2, which provides a quasi‐real hypersonic service environment at a temperature up to 2200°C. After ablation, the ablated surface is covered with oxidation products in the form of oxide layer, fibrous residues, or bubbles, which effectively isolates the sample surface from the plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 45 publications
(95 reference statements)
0
6
0
Order By: Relevance
“…In addition, EDS analysis of individual particles shows that the elements were distributed uniformly across the material on the A survey of the published literature shows that process modeling of CMCs has been studied by a number of researchers. Processes that have been modeled include RMI, 15,16 CVD, 17,18 CVI, [19][20][21][22] and Sol-Gel Infiltration. 23 Impregnation of alumina matrix in eight-harness satin Nextel 610 fabric has been studied numerically in Ref.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, EDS analysis of individual particles shows that the elements were distributed uniformly across the material on the A survey of the published literature shows that process modeling of CMCs has been studied by a number of researchers. Processes that have been modeled include RMI, 15,16 CVD, 17,18 CVI, [19][20][21][22] and Sol-Gel Infiltration. 23 Impregnation of alumina matrix in eight-harness satin Nextel 610 fabric has been studied numerically in Ref.…”
Section: Methodsmentioning
confidence: 99%
“…XRD analysis of the ablation center revealed that the oxide residuals at the ablation surface were primarily composed of A survey of the published literature modeling of CMCs has been studied by a n ers. Processes that have been modeled CVD, 17,18 CVI, [19][20][21][22] and Sol-Gel Infiltrat of alumina matrix in eight-harness satin has been studied numerically in Ref. [ proaches used in the above work general ing the flow of a high viscosity resin thr and modeling the chemical reactions and during processing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] However, in the presence of oxygen at elevated temperatures, oxidation of carbon fibers occurs and may cause excessive surface degeneration and poor mechanical properties, limiting the further development of carbon fibers as reinforcements. 6,7 It is why attention has been paid to the preparation of high-temperature coatings for carbon fibers.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon fiber‐reinforced materials, such as carbon/carbon and carbon/phenolic composites, are usually selected as thermal protection materials for aerospace vehicles 3–5 . However, in the presence of oxygen at elevated temperatures, oxidation of carbon fibers occurs and may cause excessive surface degeneration and poor mechanical properties, limiting the further development of carbon fibers as reinforcements 6,7 . It is why attention has been paid to the preparation of high‐temperature coatings for carbon fibers.…”
Section: Introductionmentioning
confidence: 99%